Bacterial Protein Toxins - Rappuoli, Rino; Ed. Burns, Drusilla L; Ed. Barbieri, Joseph T; Ed (ASM Press, 2003)
Designed for newcomers to the field of toxins and intended to show how proteins work and can be used in research. The text describes the biology of toxins, including their synthesis and secretion, their travels to and into the host cell and their modes of attacking the host cell machinery.